Austria : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report ;, 2016)
The 2015 Article IV Consultation discusses the key issues related to the economy of Austria. Austria has recovered from the global financial crisis, but the crisis still remains in bank and public sector balance sheets. Major banks have been striving to strengthen their capital and profitability positions amid regulatory and supervisory reforms. Despite lackluster growth, economic slack is limited as potential growth has fallen as well. The governing coalition of Social Democrats and the right-of-center People's Party holds a constructive dialogue on economic policy issues. Growth is estimated at 0.7 percent in 2015, a slight improvement over the 1\2 percent average in 2012-14, on the back of strengthening external and domestic demand.